Pendidikan Agama Islam di Sekolah Umum - Magdalena, Magdalena (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2013)
Undang-undang Sistem Pendidikan Nasional Nomor 20 Tahun 2003 is a law that manage all of educational system, included Islamic educational system. Based on the law, Islamic educational implementation in general school has streght and weakness. The streght of it is Islamic educational implementation as a element of the education system can help to reach the national education purpose. Meanwhile, its weakness can find for several aspect such educational result, matter and time allocation, Islamic religion teacher, environment, and Islamic learning methodology.